The market for short-term debt securities in Europe: What we know and what we do not know - Pierre-Emmanuel Darpeix (European Systemic Risk Board (ESRB), European System of Financial Supervision, 2022)
In March 2020, against the backdrop of a worsening Covid crisis, some segments of the money market fund (MMF) industry faced severe redemption pressures. Given their central role within the short term funding market, MMFs were at the heart of financial stability concerns, and legitimately underwent careful reviews by macroprudential bodies and market supervisors to assess their vulnerabilities and propose policy options to remediate them. Yet it is clear that MMFs are only one part of a wider ecosystem. These funds collect excess cash from some economic agents, which is predominantly invested in the markets for short-term debt securities, thus providing funding to a wide array of entities in need for short-term funding (banks, non-financial corporates, States, local governments, etc.). And clearly, beyond funds, vulnerabilities were also identified both on the underlying market and on the investors' side. In order to complement the recommendations issued in January 2022 by the ESRB ahead of the scheduled revision of the MMF Regulation, and so as to provide a better understanding of vulnerabilities still widely unaddressed, the AMF conducted a stock-take analysis of the public information available on the very fragmented and opaque market for short-term debt instruments in Europe. Thanks to a fruitful collaboration with ESRB who shared internal databases, it was able to fill in some data gaps and provide new insights on this market. In particular, this stock-take gives the first comprehensive and consolidated estimate of the outstanding in question (more than EUR 2.2 trillion as of Dec.2020), with a breakdown according to issuer types, instrument types and currencies. The analysis highlights the still unaddressed vulnerabilities such as the fragmentation of the market and of its supervision as well as the lack of a robust identification of Euro-CP and emphasizes the lack of transparency in the secondary market operations.
Keywords: D53; E58; E65; G15; G18; G23; H63; 330; Short term funding market; Commercial paper; Certificates of deposit; Treasury bills; STEP; NEU-CP; Euro-CP